Struktur Isi Argumen dalam Teks Argumentasi Siswa Tahap Operasi Formal - Ulfah Mey Lida (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
Text is the embodiment of one's ideas in written language that can be read and understood by the reading community. Argumentation is basically an embodiment of discourse. This study was conducted to determine the structure of the argument content in the students' argumentative essays in the formal operation stage by describing the research findings. The approach used in this study is a qualitative approach with the Miles and Huberman analysis model. The data of this research is in the form of a fragment of the student's argumentative text. This data was obtained from students' assignments to write arguments their teachers had given. In collecting data, the method used is the method of listening. The techniques used are free listening and conversation, documentation, and note-taking. The data analysis of this research uses the communication content analysis model. Based on the analysis results, it was found that the structure of the argument content of the students in the formal operation stage consisted of four structures. The four content structures are (1) deductive complex content structure, (2) inductive complex content structure, (3) deductive simple content structure, and (4) deductive complex simple content structure.